Language Choices Used by Mixed Marriage Children - Kertiana Dewi, Ni Ketut Ayu (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p08, 2018)
This paper is entitled Language Choices Used by Mixed Marriage Children. This study focuses on the strategies of communication applied by the parents in raising their children, the language frequently spoken by the children and the factors affecting the children in choosing a certain language. There are two children, Jasmine and George, being observed in this study. In this study the data were collected by direct interview with the parents and children, questionnaires, and observation. The conversations made by the children, Jasmine and George, with their parents, their aunty, the nanny and their private teacher were recorded. The collected data were analyzed by using qualitative method and descriptive technique applying the theory proposed by Romaine (1995) and Holmes (2001). As a result of this study, strategy 1: ‘one person-one language’ is successfully applied by the parents in this family in raising their bilingual children. They communicate with their own language to the children from birth. So, the children, Jasmine and George, fluently speak two languages, namely Indonesian and English. However, English is the language spoken more frequently by the children and the children in this study know with whom to talk certain languages according to the participants, settings and topics.